PROFIL PENGOBATAN PASIEN DIABETES MELITUS TIPE 2 KARTU JAKARTA SEHAT YANG MENJADI PASIEN BPJS DI RSUD TARAKAN JAKARTA - Erlana, Nanang (SOCIAL CLINICAL PHARMACY INDONESIA JOURNAL, 2017)
Kartu Jakarta sehat (KJS) is also a health care insurance program provided by the Provincial Government of DKI Jakarta through UP Jamkesda (Regional Health Insurance) DKI Jakarta Provincial Health Office to the community in the form of medical assistance using Essential Service Package / PPE method. DKI Jakarta Provincial Government, has merged the Kartu Jakarta Sehat (KJS) with National Health Insurance (JKN) which was officially applied as of January 1, 2014. The owner of Jamkesda DKI card / Kartu Jakarta Sehat which is a free health program for the poor, BPJS Health. Diabetes Mellitus is one of the chronic diseases that require comprehensive services and the number is always increasing every year. Treatment of Diabetes Mellitus should be done routinely and the outcome of therapy or clinical outcome needs to be monitored in a planned manner. The purpose of this research is to know the difference of treatment profile before and after the implementation of JKN in patient of Diabetes Mellitus type 2 Kartu Jakarta Sehat in RSUD Tarakan Jakarta. The study was conducted in longitudinal time series, restrospectively collecting data from patient medical records and Hospital Pharmacy Installations from January 2013 to December 2014 for patients who met the inclusion criteria. The results showed no difference in total drug, DM drug, non-DM drug, generic drug and drug of Fornas. Based on these results it can be concluded that the profile of treatment in patients with type 2 diabetes Kartu Jakarta Sehat did not change after the implementation of  National Health Insurance (JKN).